Percobaan Interaktif Menggali Misteri Pelangi untuk Meningkatkan Keterampilan Proses Sains Anak Usia Dini - Cici Nuriah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
This article focuses on the discussion of research regarding efforts to improve science skills in children through an interactive theme park with the theme of the universe with a rainbow sub-theme. This interactive experiment can use teachers and parents as an interesting and fun strategy learning process by involving children directly and trying experiment activities themselves to explore deeper understanding. This study aims to improve science process skills in group B children in PAUD Bambim An-Nur, Kawalu Tasikmalaya through the implementation of interactive experiments. This research used Classroom Action Research (PTK) with a design model designed by Stephen Kemmis and Taggart through four steps consisting of planning, action, observation, and reflection. This research was completed through pre-cycle observations and 2 action cycles with 5 types of experimental activities in April-May 2023. The results obtained data on improving science process skills in children through interactive experiments. In cycle I, children's development in science process skills is in the Good criteria with an average proportion of 69%. Then in cycle II, the process of developing science skills occupies a very good position with an average proportion of 78%. From these results it can be said that interactive experiments exploring the mystery of the rainbow have succeeded in significantly increasing children's science process skills.